Synthesis, Characterization, and Photocatalytic Activity of Sb2O3 Nanoparticles: A Step towards Environmental Sustainability - Sabeeha Jabeen; Ekhlakh Veg; Shashi Bala; Tahmeena Khan (Engineering Proceedings, 2024)
Various nano-photocatalysts have been used to decompose organic dyes. Sb2O3 nanoparticles (NPs) have emerged as potential photocatalysts due to their redox potential, non-toxicity, long-term stability, and low cost. This work describes the fabrication of Sb2O3 NPs via the solvothermal process. A field emission scanning electron microscopic (FE-SEM) analysis depicted the spherical shape of the NPs, and an energy-dispersive X-ray (EDAX) analysis confirmed the presence of oxygen (O) and antimony (Sb) in the synthesized NPs. XRD (X-ray diffraction) patterns were recorded to measure the size and phase of the NPs. The sample was found with an alpha phase of antimony oxide indicating high purity. The Scherrer equation was used to calculate the size of the NPs, which was found to be approximately 20.89 nm. The photocatalytic potential was tested against methylene blue (MB) dye. The NPs showed a 60% degradation of the dye in 60 min. The dye was found to be adsorbed on the Sb2O3 nanoball surface and degradation was associated with the generation of reactive oxygen species (ROS).